ENHANCING STUDENTS' UNDERSTANDING OF PAST TENSE THROUGH QUIZIZZ: A GAME-BASED EDUCATIONAL TOOL - Heri Miarto; Haris Dibyaningsih (Journal of English Language Teaching and Islamic Integration, 2024)
Quizizz is a game-based educational platform. Quizizz becomes one of educational technology most applied since the pandemic of Covid-19. It provides both lives and assignment quiz. Since the past tense is one of important grammar that can help students to deliver their ideas about past event or experience. This paper will explore some steps of using Quizizz in teaching Past Tense. Moreover, this paper describes the benefit of Quizizz in upgrading students’ past tense understanding. Finally, the paper hopefully can help teachers in creating interactive quiz in teaching Past tense.